2011
DOI: 10.1089/ten.tec.2010.0417
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Three-Dimensional Volumes of Interest with Adapted Surfaces for More Precise Subchondral Bone Analyses by Micro-Computed Tomography

Abstract: Micro-computed tomography can be used to analyze subchondral bone features below treated cartilage defects in animal models. However, standardized methods for generating precise three-dimensional (3D) volumes of interest (VOI) below curved articular surfaces are lacking. The aims of this study were to develop standardized 3D VOI models adapted to the curved articular surface, and to characterize the subchondral bone specifically below a cartilage defect zone in intact and defect femoral trochlea. Skeletally ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 23 publications
(32 reference statements)
0
31
1
Order By: Relevance
“…The subchondral bone microarchitecture can be assessed by histomorphometric (Parfitt et al, 1987) or threedimensional radiological techniques (Feldkamp et al, 1989;Marchand et al, 2011;Orth et al, 2012b).…”
Section: Changes In Subchondral Bone Microarchitecturementioning
confidence: 99%
See 3 more Smart Citations
“…The subchondral bone microarchitecture can be assessed by histomorphometric (Parfitt et al, 1987) or threedimensional radiological techniques (Feldkamp et al, 1989;Marchand et al, 2011;Orth et al, 2012b).…”
Section: Changes In Subchondral Bone Microarchitecturementioning
confidence: 99%
“…The work of Hoemann and Buschmann (Chen et al, 2009;Chen et al, 2011a;Chen et al, 2011b;Marchand et al, 2011;Marchand et al, 2012) revealed that lapine subchondral bone surrounding drill holes remains morphologically intact at day 1, while empty osteocyte lacunae surround microfracture holes (Chen et al, 2009). Regarding the drilling instrument itself, drills may be superior to Kirschner wires, which do not remove bone The subchondral bone in cartilage repair debris -thus possibly impeding the migration of stem cells (Chen et al, 2009).…”
Section: Changes In Subchondral Bone Microarchitecturementioning
confidence: 99%
See 2 more Smart Citations
“…Hitherto, there has been no serious evaluation of the relative benefits (or risks) of considering a particular regular geometric VOI (cylindrical, spheric, cubic) vs. manually marked (adapted) scanning zone. Yet, certain advantages of using "adapted VOIs" were suggested, as simple geometric VOI shapes cannot encompass all the bone tissue within a desired zone [4].…”
mentioning
confidence: 99%